Dimensional accuracy in dry micro wire electrical discharge machining - Ali, Mohammad Yeakub; Banu, Asfana; Salehan, Muhammad; Adesta, Erry Yulian Triblas; Hazza Faizi Al Hazza, Muataz; Shaffiq, Muhammad (Pusat Teknologi Maklumat & Komunikasi, Universiti Malaysia Pahang, 2018)
Dimensional accuracy is important in fabricating miniaturized product in order to reduce the material waste and machining cost as well as to achieve a better quality product. This paper presents the analysis and modelling of dimensional accuracy in dry micro wire electrical discharge machining with control parameters of gap voltage and wire tension. The investigation was performed on stainless steel using integrated multi-process micro machine tools DT 110 with compressed air as the dielectric fluid and tungsten as the wire electrode. The dimensional accuracy was determined through kerf width differences of the machined slots. The kerf width was measured using scanning electron microscope. Full factorial was used to design the experiment while analysis of variance (ANOVA) was used to analyse the results as well as to evaluate the adequacy of the developed model. Based on ANOVA, both parameters; gap voltage and wire tension have high influence on kerf width differences. The optimum machining parameters for minimum kerf width differences were found to be 85 V gap voltage and 10 % wire tension. The developed model is adequate since the percentage error (2.13 %) is relatively small. It is recommended that different type of gases should be used for further investigation in order to determine the accuracy of the dry micro wire EDM.